Pengaruh Pengetahuan Sanitasi Higiene Terhadap Perilaku Higiene Siswa Kuliner SMK Negeri 1 Lamongan - Rika Aprilia; Asrul Bahar; Sri Handajani; Lilis Sulandari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine the effect of sanitation hygiene knowledge on the hygiene behavior intention of culinary students in SMK. The type of research used in this study is quantitative with an evaluative descriptive approach. Descriptive evaluative research is research conducted to investigate circumstances, conditions, situations, events, activities, and others whose results will be compared with criteria and conclusions drawn. The population of this study were X and XI grade culinary students of SMK Negeri 1 Lamongan, totaling 30 students selected using simple random sampling technique. The instrument used is a knowledge test question in the form of multiple choice of 20 questions which is used to measure the level of student knowledge and observation sheets to see student hygiene behavior at school. This study uses simple regression test analysis, the instrument is calculated using SPSS 25 and can be said to be valid if r count> 3.361. for the reliability test, the results are said to be reliable if Cronbach's Alpha> 0.60. In this study, the reliability value is 0.708. The results showed that 2 students' sanitation hygiene knowledge was in the low category (6.7%), 5 students in the moderate category (16.7%), 8 students in the good category (26.7%) and 15 students in the excellent category (50%). For hygiene behavior intention, 13 students were in the very good category with a percentage of 43.3% and there were 17 students in the good category with a percentage of 56.7%. The results showed that sanitation hygiene knowledge affects students' hygiene behavior with a large influence on the R Square value obtained of 26.5%.